Phytochemical Screening and Antibacterial Activity of Stem Bark of Baobab Tree (Adonsonia digitata) on some clinical isolate - Ummu Rabi’u, RA; Sa’idu, Haruna; Labaran, Hajara Sani; Olanrewaju, Salau Abiola; Muntari, Musa; Ibrahim, Sani Aliyu (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
The use of plant and their secondary metabolite for the treatment of several illnesses is gaining attention across the globe. For this reason, baobab tree was procured in order to test its effect on some bacterial isolate. Powdered stem bark of Adansonia digitata was extracted with chloroform and methanol using percolation method of extraction. The extracts were dark brown and reddish brown in color respectively with a gummy texture. The chloroform and methanolic extracts were screened from the presence of secondary metabolites using standard technique. The result of photochemical screening indicated the presence of alkaloid, flavonoid, tannin, reducing sugar and steroid in one or both the extracts. The extracts were further tested, on confirmed clinical isolates of Salmonella typhi and Staphylococcus aureus using disc diffusion method and micro â€“ broth dilution technique. The result of sensitivity test indicated that the tested clinical isolates were more sensitive to chloroform extract than the methanolic extract because larger zones of inhibitions were obtained with chloroform extract. In both methods used, the organisms were susceptible to all extracts even at the lowest concentration of 15 ïg with zones of inhibitions ranging from (8 â€“ 10 mm).